2017
DOI: 10.1302/1863-2548.11.160208
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia epiphysealis hemimelica: A histological comparative study with osteochondromas

Abstract: PurposeDysplasia epiphysealis hemimelica (DEH) is a rare developmental disorder resulting in epiphyseal overgrowth. Based on histological appearance, it is often described as an osteochondroma or osteochondroma-like lesion, although clinical differences exist between DEH and osteochondromas. The aim of this study was to test whether DEH and osteochondromas are histologically identical diseases.MethodsTissue samples of two age- and gender-matched cases with DEH and hereditary multiple exostoses were histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Although it has been described as a rare developmental disorder, recent research has greatly advanced our understanding of the pathobiology and articular involvement of DEH. Erroneously described as an osteochondroma or osteochondroma-like lesion despite its epiphyseal location, some studies demonstrated that DEH lesions differ pathologically from osteochondromas [9, 15]. In a comparative histological study, Stevens et al found that in DEH lesions chondrocyte clusters are seen in conjunction with a thick disorganized cartilage cap and ossification centers with small amounts of unabsorbed cartilage, whereas in osteochondroma lesions cartilage is more organized and displays characteristics of the normal growth plate [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it has been described as a rare developmental disorder, recent research has greatly advanced our understanding of the pathobiology and articular involvement of DEH. Erroneously described as an osteochondroma or osteochondroma-like lesion despite its epiphyseal location, some studies demonstrated that DEH lesions differ pathologically from osteochondromas [9, 15]. In a comparative histological study, Stevens et al found that in DEH lesions chondrocyte clusters are seen in conjunction with a thick disorganized cartilage cap and ossification centers with small amounts of unabsorbed cartilage, whereas in osteochondroma lesions cartilage is more organized and displays characteristics of the normal growth plate [15].…”
Section: Discussionmentioning
confidence: 99%
“…Erroneously described as an osteochondroma or osteochondroma-like lesion despite its epiphyseal location, some studies demonstrated that DEH lesions differ pathologically from osteochondromas [9, 15]. In a comparative histological study, Stevens et al found that in DEH lesions chondrocyte clusters are seen in conjunction with a thick disorganized cartilage cap and ossification centers with small amounts of unabsorbed cartilage, whereas in osteochondroma lesions cartilage is more organized and displays characteristics of the normal growth plate [15]. In addition, differently from osteochondroma lesions, collagen type II is weakly expressed and collagen type X is not detected in DEH lesions [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also has been reported that EXT1 and EXT2 were found in osteochondroma by genetic examination, that may provide an appropriate evidence when two pathological examinations are similar. [12]…”
Section: Discussionmentioning
confidence: 99%